دور تعليم اللغة الأم كطريقة تعلم اللغة العربية لغير الناطقين بها - Jafar Sidik; Lina Husnul Karimah (Program Studi Pendidikan Bahasa Arab (PBA), Fakultas Tarbiyah dan Ilmu Keguruan (FTIK), Instutut Agama Islam Negeri (IAIN) Palu, 2022)
Mother tongue is the language that a person acquires when he or she knows a language for the first time. The Mother tongue has a strong influence on the sound formation and word formation in learning other languages. This research using the library research method aims to find out the role of mother tongue teaching that can be implemented as a method of teaching Arabic for non-native speakers. The results of this research found that mother’s tongue teaching can be implemented as a method of learning Arabic for non-native speakers.